External hard particle size effect on changes in frictional performance and grit embedment during drag and stop mode braking - Abdul Hamid, M.; Abu Bakar, A.; Stachowiak, Gwidon (2014)
The effects of silica sand of 50-180 µm, 180-355 µm and 355-500 µm on friction performance and grit embedment at brake disc and pad interface was investigated. Results showed that present of external hard particles caused higher friction coefficient due to higher number of smaller particles involved in mixing and changing the effective contact, while good friction stability was attributed to smaller grit particles and compacted wear debris. Grit embedment was greatly dependent on presence of compacted wear debris as most grits were embedded into compacted wear debris with embedment of 0.8% was observed for 50-180 µm, 2% for 180-355 µm and 3% for 355-500 µm.